PEMBERDAYAAN PENDIDIKAN DASAR - Sholeh, Ahmad (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2009)
The empowering in primary education includes all of the aspects which aim to improve the quality of education either in teaching-learning process, curriculum, management or others. If we observe primary education especially in state primary education, we will find some weaknesses. Therefore to solve the problem, we must implement the planning of community-based education and decentralization of education from grass root optimally. Because the results of the analyzing showed that the implementations of planning have significance to survive the institution for the future. Keyword: Empowering, community-based education, grass root